The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ani10122363
|View full text |Cite
|
Sign up to set email alerts
|

Development and Field Validation of Lidocaine-Loaded Castration Bands for Bovine Pain Mitigation

Abstract: Castration is among the most common management procedures performed in the dairy and beef cattle industries and is mainly performed by surgery or elastic banding. Despite the various benefits of castration, all methods produce pain and distress. Castration by banding is simple, inexpensive, produces fewer complications, and can be performed in a high-throughput manner. Because lidocaine, a local anesthetic, can be delivered to trauma sites topically, we have formulated lidocaine-loaded castration bands (LLBs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 18 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…Dimenhydrinate and tavaborole displayed a very strong initial burst release over 1 day (Figure S7F,G), while salicylic acid displayed first order release kinetics closer to those of lidocaine (Figure S7H). ,, We investigated the function of the SIS bands and released drug via cell culture studies. At first, the effect of salicylic acid released was measured from the SIS bands on cell viability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dimenhydrinate and tavaborole displayed a very strong initial burst release over 1 day (Figure S7F,G), while salicylic acid displayed first order release kinetics closer to those of lidocaine (Figure S7H). ,, We investigated the function of the SIS bands and released drug via cell culture studies. At first, the effect of salicylic acid released was measured from the SIS bands on cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, drugs that exhibited good loading and release behaviors in this work were soluble in chloroform and at least slightly soluble in water. 14,34,35 We showed that the bands released functional drugs to affect both cell and animal models. Finally, we found that SIS bands can be used for binding of enteric tissue, as in hemorrhoid ligation, and that drugs could be released into the local tissue at therapeutic concentrations.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…All methods of castration at any age in any species are painful [ 86 , 87 , 88 ]. There is minimal evidence of analgesia efficacy for surgical castration in pigs with any of the currently approved NSAIDs or local anesthetics, such as lidocaine [ 52 , 89 , 90 , 91 ], and some evidence of partial efficacy for analgesia following castration by band or surgical means in beef cattle [ 92 , 93 ]. In general, there is a lack of information about analgesia efficacy for surgical castration of sheep and few licensed analgesic drugs available for use [ 94 ] in this species.…”
Section: Treatment Of Pain In Farm Animals For Routine Proceduresmentioning
confidence: 99%
“…In one study, an analgesic benefit was observed after the administration of morphine and flunixin meglumine [ 45 ]. One promising analgesia technique that has been recently described is the use of lidocaine-loaded castration bands in 3–4-week-old beef calves [ 92 ]. This method provides sustained transcutaneous release of local anesthetic within the scrotal tissues while the band is in place.…”
Section: Treatment Of Pain In Farm Animals For Routine Proceduresmentioning
confidence: 99%